THE RELATIONSHIP BETWEEN THE STRUCTURE OF PHASE EQUILIBRIUM DIAGRAM AND THE STRUCTURE OF FLOWSHEET DIAGRAMS OF MULTIPHASE QUATERNARY MIXTURES SEPARATION - A. Yu. Sebyakin; A. K. Frolkova (Тонкие химические технологии, 2016)
In this work the structures of phase equilibrium diagrams of multiphase four-component systems n-hexane (n-heptane, n-octane) - cyclohexane - furfural - water were investigated. The systems are characterized by the existence of areas of three-phase separation. On the basis of the obtained data the synthesis of feasible variants of separation schemes was carried out, rational modes of functioning of each column were found, the energetically favorable variant was chosen. It was found that the use of preliminary phase separation in systems with n-hexane and n-octane is power-efficient, and the profit in case of the octane system (equimolar mixture) in comparison with the application of the first predetermined separation at the first stage is more than 25%. Certain difficulties (the high values of columns effectiveness: 60 and 40 theoretical plates) upon the separation of the hexane and heptane systems are due to the similar volatilities of n-hexane (n-heptane) and cyclohexane in the vicinity of the point of pure alkane.